Management of Acute Coronary Syndrome in the Older Adult Population: A Scientific Statement From the American Heart Association - Damluji, Abdulla A; Forman, Daniel E; Wang, Tracy Y; Chikwe, Joanna; Kunadian, Vijay; Rich, Michael W; Young, Bessie A; Page, 2nd, Robert L; DeVon, Holli A; Alexander, Karen P (Circulation (New York, N.Y.), 2023)
Diagnostic and therapeutic advances during the past decades have substantially improved health outcomes for patients with acute coronary syndrome. Both age-related physiological changes and accumulated cardiovascular risk factors increase the susceptibility to acute coronary syndrome over a lifetime. Compared with younger patients, outcomes for acute coronary syndrome in the large and growing demographic of older adults are relatively worse. Increased atherosclerotic plaque burden and complexity of anatomic disease, compounded by age-related cardiovascular and noncardiovascular comorbid conditions, contribute to the worse prognosis observed in older individuals. Geriatric syndromes, including frailty, multimorbidity, impaired cognitive and physical function, polypharmacy, and other complexities of care, can undermine the therapeutic efficacy of guidelines-based treatments and the resiliency of older adults to survive and recover, as well. In this American Heart Association scientific statement, we (1) review age-related physiological changes that predispose to acute coronary syndrome and management complexity; (2) describe the influence of commonly encountered geriatric syndromes on cardiovascular disease outcomes; and (3) recommend age-appropriate and guideline-concordant revascularization and acute coronary syndrome management strategies, including transitions of care, the use of cardiac rehabilitation, palliative care services, and holistic approaches. The primacy of individualized risk assessment and patient-centered care decision-making is highlighted throughout.